Intravitreal lower- dose (20 mu g) melphalan for persistent or recurrent retinoblastoma vitreous seeds - Tuncer, Samuray; Balcı, Özlem; Tanyıldız, Burak; Kebudi, Rejin; Shields, Carol (Slack Incorporated, 2015)
BACKGROUND AND OBJECTIVE: The major cause of failure in the management of retinoblastoma is the persistence/recurrence of vitreous seeds (VS). This study reports the efficacy and complications of standard lower-dose (20 mu g) intravitreal melphalan for VS. PATIENTS AND METHODS: Retrospective review of all patients with active VS treated with lower-dose intravitreal melphalan (20 mu g/0.1 mL) on a monthly basis until complete VS regression was achieved. RESULTS: A total of 14 injections were delivered to seven eyes of seven patients (range: 1-4; median: 2). At a median follow-up of 20 months (range: 12-32 months), complete regression of VS was achieved in all cases (100%), and globe salvage was achieved in six cases (86%). One eye required enucleation for solid tumor recurrence. Side effects of retinal pigment epithelium mottling at the site of injection was noted in two eyes (29%). CONCLUSION: The 2-year results of this study suggest that standard lower-dose (20 mu g) intravitreal melphalan is safe and highly effective for the management of viable VS from retinoblastoma.
WOS: 000378842200007
PubMed ID: 26469234
Keywords: Retinoblastoma; Intravitreal Melphalan